Pemberdayaan Anak Yakub : Pendekatan Teologis untuk Pendidikan, Karakter, dan Kepedulian Sosial Pasca-Pandemi di Silangkitang - Patricia Dwi Irwani Telaumbanua; Irfan Firma Tua Berutu; Putri Natalia Sihite (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Jacob Children's Community is a service initiative that was formed as a response to the challenges faced by children in the Silangkitang area after the COVID-19 pandemic. The main focus of this community is to provide holistic education that includes academic, spiritual and character building aspects. The facilitators try to overcome the impact of social isolation and dependence on devices experienced by children by holding teaching activities, Bible studies, as well as moral and environmental awareness training. Through inclusive and love-based methods, this community plays an important role in forming a generation that is not only intelligent, but also has character and cares about the surrounding environment. This article discusses theological reflections on the services carried out in this community, referring to Biblical values ​​and the views of theologians such as John Wesley and Dietrich Bonhoeffer, who emphasized the importance of education as a means of forming faith and character. The Jacob's Children Community makes a significant contribution in facing post-pandemic social challenges by educating and developing children through a comprehensive and loving approach.